Estimation of Iron Availability in Modified Cereal β-Glucan Extracts by an in vitro Digestion Model - Marasca, Elena; Zehnder-Wyss, Olivia; Boulos, Samy; Nyström, Laura (Frontiers in Nutrition, 2022)
For cereal-based foods rich in dietary fibers, iron bioavailability is known to be poor. For native cereal β-glucan extracts, literature has demonstrated that the main factor impacting the bioavailability is phytic acid, which is often found in association with dietary fibers. During food processing, β-glucan can undergo modifications which could potentially affect the equilibrium between phytic acid, fiber and iron. In this study, an in vitro digestion was used to elucidate the iron-dialysability, and hence estimate iron-availability, in the presence of native, chelating resin (Chelex)-treated, oxidised, or partially hydrolysed oat and barley β-glucan extracts (at 1% actual β-glucan concentration), with or without phytase treatment. It was confirmed that pure, phytic acid-free β-glucan polysaccharide does not impede iron-availability in cereal foods, while phytic acid, and to a smaller extent, also proteins, associated to β-glucan can do so. Neither Chelex-treatment nor partial hydrolysis, TEMPO- or NaIO4-oxidation significantly influenced the phytic acid content of the β-glucan extracts (ranging 2.0–3.9%; p > 0.05). Consequently, as long as intrinsic phytic acid was still present, the β-glucan extracts blocked the iron-availability regardless of source (oat, barley) or Chelex-treatment, partial hydrolysis or NaIO4-oxidation down to 0–8% (relative to the reference without β-glucan extract). Remarkably, TEMPO-oxidation released around 50% of the sequestered iron despite unchanged phytic acid levels in the modified extract. We propose an iron mobilizing effect of the TEMPO product β-polyglucuronan from insoluble Fe(II)/ phytate/ protein aggregates to soluble Fe(II)/bile salt units that can cross the dialysis membrane. In addition, Chelex-treatment was identified as prerequisite for phytase to dramatically diminish iron retention of the extract for virtually full availability, with implications for optimal iron bioavailability in cereal foods.